2015
DOI: 10.4236/graphene.2015.44010
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cu-Exfoliated Graphite Nanoplatelets (xGnP) Metal Matrix Composite by Powder Metallurgy Route

Abstract: In the present investigation the possibility of using exfoliated graphite nanoplatelets (xGnP) as reinforcement in order to enhance the mechanical properties of Cu-based metal matrix composites is explored. Cu-based metal matrix composites reinforced with different amounts of xGnP were fabricated by powder metallurgy route. The microstructure, sliding wear behaviour and mechanical properties of the Cu-xGnP composites were investigated. xGnP has been synthesized from the graphite intercalation compounds (GIC) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…The raw and ground graphite had I D / I G ratios of 0.039 and 0.094, respectively. This slight increase in the I D / I G ratio supported the occurrence of delamination of the ground graphite and suggested that mechanical grinding only resulted in a low extent of defects . The 2D peaks of the two samples were at about 2693 cm −1 , with a shoulder at a lower Raman shift similar to the typical graphite 2D‐band feature reported earlier .…”
Section: Resultssupporting
confidence: 80%
“…The raw and ground graphite had I D / I G ratios of 0.039 and 0.094, respectively. This slight increase in the I D / I G ratio supported the occurrence of delamination of the ground graphite and suggested that mechanical grinding only resulted in a low extent of defects . The 2D peaks of the two samples were at about 2693 cm −1 , with a shoulder at a lower Raman shift similar to the typical graphite 2D‐band feature reported earlier .…”
Section: Resultssupporting
confidence: 80%
“…The chemical approach for producing GO is well suited for mass production because of its low-cost procedure. Furthermore, it can render a large variety of different variants of graphene with chemical modifications [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the peak appears considerably smaller and broader. That indicate that inter planar distance in xGnP is similar to the parent pristine graphite, but the stack size of graphene layers is small [6].…”
Section: X-ray Diffraction Analysismentioning
confidence: 93%